1971
DOI: 10.2466/pr0.1971.29.2.651
|View full text |Cite
|
Sign up to set email alerts
|

On the Reluctance to Communicate Undesirable Messages (The MUM Effect): A Field Study

Abstract: The present study generalized a previously observed reluctance to transmit bad news to a field situation in which the conveying of bad news is a natural, recurring phenomenon. In a sample of 27 applicants for aid to the disabled, the time taken to communicate the agency's decision to the client was longer if the decision was to deny aid than if it was to grant aid ( p < .08).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 1 publication
3
47
0
1
Order By: Relevance
“…These results were as expected and indicated that subjects anticipated that positive statements would be easier to deliver than negative statements. These results support Tesser et al's ( 1971) contention that persons are reluctant to communicate negative information-the so-called &dquo;Mum Effect.&dquo;…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These results were as expected and indicated that subjects anticipated that positive statements would be easier to deliver than negative statements. These results support Tesser et al's ( 1971) contention that persons are reluctant to communicate negative information-the so-called &dquo;Mum Effect.&dquo;…”
Section: Resultssupporting
confidence: 84%
“…Such re- Mean Impact Scores for Valence x Type by Deliverer Sex Interaction sults strongly support the contention of Tesser et al ( 1971) that people are extremely reluctant to give negative information to other people. If offered a choice, people will choose to give positive information to one another.…”
Section: Round IIsupporting
confidence: 64%
“…It is often characterized as the ability to ''put oneself into another's shoes''. These behaviors by the bearers of bad news may stem from the difficulties of the person delivering the news [22][23][24], but the strong emotions evoked in these cases serve to remind us of the importance of following the principles of the correct strategy for the breaking of bad news.…”
Section: Discussionmentioning
confidence: 97%
“…The bearer of bad news often experiences strong emotions such as anxiety, a burden of responsibility for the news and fear of negative evaluation [22][23][24]. This stress creates a reluctance to deliver bad news.…”
Section: Discussionmentioning
confidence: 98%
“…The authors also describe how these conversations can be difficult to both initiate and conduct well, and can be significantly tainted by our own emotions. The guilt that we feel over our "failure" to cure the cancer can permeate into these discussions, make them stressful for us and the patient, and make us likely to avoid them altogether [4]. Indeed, for surgeons devoted to the care of cancer, our years of surgical training and our necessary belief in our surgical skills may contribute to our difficulty in admitting failure.…”
mentioning
confidence: 99%